De sacrale Wereld van de Turkana. Ritueel, symbool en mythe bij een nomadenvolk in Noordwest Kenya - Wymeersch, Patrick; Berben, Patrick; Bogers, Koen (Afrika Focus, 1994)
Tlüs article was mostly written by the late Patrick Wymeersch and was meant to be the onset to a broader monographical sketch of the religious world of the Turkana, a nomadic group of north-west Kenya. Attention is drawn to the organisation of the Turkana society and to several rituals which form the basis of the daily life environment. Furthermore the authors looked at the phenomena of the "Ngamoritunga " rocks and the position and the role of "Ang'u".One last word goes to the value of symbols within that society. KEY WORDS: Turkana, religion, rituals, symbols.